SITUATION CONTEXT OF THE DESCRIPTIVE TEXT OF THE SPEECH BY THE CHINESE LEADER AT THE G20 SUMMIT ON NOVEMBER 15, 2022 - Alvionita Alindra, Devi (ELT (English Language Teaching Prima Journal), 2024)
Understanding the interplay between language and situational context is paramount in exploring the depth of meaning within descriptive texts. This study delves into the language utilized in descriptive texts to depict objects, places, or events with vivid detail, allowing readers to immerse themselves in the described experiences. Moreover, the situational context encompasses factors like communication purpose, audience, social and cultural context, place and time context, and the author's experience and perspective. Using discourse analysis, this article examines the situational context in the descriptive text of the speech by the Chinese leader at the G20 Summit on November 15, 2022. The research method employed in this study is qualitative research with a descriptive approach. The study focuses on three dimensions: discourse field, discourse participants, and discourse devices. By analyzing these aspects, the article sheds light on how language and context influence the formation, distribution, and interpretation of messages within discourse, offering a comprehensive understanding of communication dynamics and meaning formation in society.